If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 = (x + -14)(x + -5) Reorder the terms: 35 = (-14 + x)(x + -5) Reorder the terms: 35 = (-14 + x)(-5 + x) Multiply (-14 + x) * (-5 + x) 35 = (-14(-5 + x) + x(-5 + x)) 35 = ((-5 * -14 + x * -14) + x(-5 + x)) 35 = ((70 + -14x) + x(-5 + x)) 35 = (70 + -14x + (-5 * x + x * x)) 35 = (70 + -14x + (-5x + x2)) Combine like terms: -14x + -5x = -19x 35 = (70 + -19x + x2) Solving 35 = 70 + -19x + x2 Solving for variable 'x'. Combine like terms: 35 + -70 = -35 -35 + 19x + -1x2 = 70 + -19x + x2 + -70 + 19x + -1x2 Reorder the terms: -35 + 19x + -1x2 = 70 + -70 + -19x + 19x + x2 + -1x2 Combine like terms: 70 + -70 = 0 -35 + 19x + -1x2 = 0 + -19x + 19x + x2 + -1x2 -35 + 19x + -1x2 = -19x + 19x + x2 + -1x2 Combine like terms: -19x + 19x = 0 -35 + 19x + -1x2 = 0 + x2 + -1x2 -35 + 19x + -1x2 = x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -35 + 19x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. 35 + -19x + x2 = 0 Move the constant term to the right: Add '-35' to each side of the equation. 35 + -19x + -35 + x2 = 0 + -35 Reorder the terms: 35 + -35 + -19x + x2 = 0 + -35 Combine like terms: 35 + -35 = 0 0 + -19x + x2 = 0 + -35 -19x + x2 = 0 + -35 Combine like terms: 0 + -35 = -35 -19x + x2 = -35 The x term is -19x. Take half its coefficient (-9.5). Square it (90.25) and add it to both sides. Add '90.25' to each side of the equation. -19x + 90.25 + x2 = -35 + 90.25 Reorder the terms: 90.25 + -19x + x2 = -35 + 90.25 Combine like terms: -35 + 90.25 = 55.25 90.25 + -19x + x2 = 55.25 Factor a perfect square on the left side: (x + -9.5)(x + -9.5) = 55.25 Calculate the square root of the right side: 7.433034374 Break this problem into two subproblems by setting (x + -9.5) equal to 7.433034374 and -7.433034374.Subproblem 1
x + -9.5 = 7.433034374 Simplifying x + -9.5 = 7.433034374 Reorder the terms: -9.5 + x = 7.433034374 Solving -9.5 + x = 7.433034374 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9.5' to each side of the equation. -9.5 + 9.5 + x = 7.433034374 + 9.5 Combine like terms: -9.5 + 9.5 = 0.0 0.0 + x = 7.433034374 + 9.5 x = 7.433034374 + 9.5 Combine like terms: 7.433034374 + 9.5 = 16.933034374 x = 16.933034374 Simplifying x = 16.933034374Subproblem 2
x + -9.5 = -7.433034374 Simplifying x + -9.5 = -7.433034374 Reorder the terms: -9.5 + x = -7.433034374 Solving -9.5 + x = -7.433034374 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9.5' to each side of the equation. -9.5 + 9.5 + x = -7.433034374 + 9.5 Combine like terms: -9.5 + 9.5 = 0.0 0.0 + x = -7.433034374 + 9.5 x = -7.433034374 + 9.5 Combine like terms: -7.433034374 + 9.5 = 2.066965626 x = 2.066965626 Simplifying x = 2.066965626Solution
The solution to the problem is based on the solutions from the subproblems. x = {16.933034374, 2.066965626}
| 8=9-3y | | 11/2-1/7 | | -7x-5+4x=-4 | | t/3-4=16 | | 14-4p=9 | | -5z+13=7+3 | | 8=6-5b | | x^3+5x=-7 | | x^3-5x=-7 | | x^3+5x+7=0 | | (x)(0.4)=y | | 7m+3=3m+20 | | -8=-4(-6x-3) | | X-20+x-10=x+20 | | r/1.5=24 | | -(7x-35)=7 | | 3x+15=x+20+x+25 | | y=5(sin(5x)) | | 5x+10y=420 | | 18(x)-4=120 | | 3y=7x*15 | | 250(2x+x)=3500 | | 18(x)+4=120 | | 8x-40=5(4+5x)+8 | | 4b-2=2(1+2b)+2b | | -2x-5x+5=0 | | d/dx(7lnx) | | 3x^2-xy+12=0 | | 0=2xcos(x)-x | | (7^-2)/(4x^-3) | | 8a^2=6a | | 12-7(x-9)=75+bx |